FE2AT - Finite element informed atomistic simulations - Möller, Johannes; Prakash, Aruna; Bitzek, Erik (Modelling and Simulation in Materials Science and Engineering, 2013)
Atomistic simulations play an important role in advancing our understanding of the mechanical properties of materials. Currently, most atomistic simulations are performed using relatively simple geometries under homogeneous loading conditions, and a significant part of the computer time is spent calculating the elastic response of the material, while the focus of the studies lies usually on the mechanisms of plastic deformation and failure. Here we present a simple but versatile approach called FE2AT to use finite element calculations to provide appropriate initial and boundary conditions for atomistic simulations. FE2AT allows us to forgo the simulation of large parts of the elastic loading process, even in the case of complex sample geometries and loading conditions. FE2AT is open source and can be used in combination with different atomistic simulation codes and methods. Its application is demonstrated using the bending of a nano-beam and the determination of the displacement field around a crack tip as examples.
WW1::963